The Essence of the Middle Class: A Review of Poulantzas’s Classes in Contemporary Capitalism - Badridduja, Faiz (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Extract This review examines Nicos Poulantzas’s Classes in Contemporary Capitalism as an important work for understanding the relationship between social class, state apparatuses, and the dynamics of modern capitalism. Poulantzas argues that social class cannot be understood solely in economic terms, but must also be analysed through political, ideological, and class struggle dimensions. He further shows that state apparatuses, especially ideological apparatuses such as education, religion, and the media, play a central role in maintaining and reproducing class positions within capitalist society. Through his discussion of the bourgeoisie, the contradictions of monopoly capitalism, and the dilemma of the new petty bourgeoisie, the book offers a sharp framework for interpreting the middle class as a significant buffer group that lacks full political and ideological autonomy. In the Indonesian context, Poulantzas’s ideas are particularly relevant for understanding the Muslim middle class, which has developed through Islamic education, pesantren, digital media, religious lifestyles, and the commodification of religion. The book is therefore valuable not only for reading European capitalism, but also for providing a theoretical foundation for interpreting contemporary socio religious phenomena in Indonesia.